THE ROLE OF MOTIVATION IN SECOND LANGUAGE ACQUISITION - Karimberganova Shahnoza Muxammad qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Motivation  is  considered  one  of  the  most  salient  psychological constituents that significantly affect second language acquisition. Indeed, motivation significantly determines the extent of involvement, effort, and tenacity that learners must exhibit in the language learning process. Moreover, the abstract touches upon the roles  of  different  internal  and  external  factors  that  play  a  pivotal  role  in  shaping motivation, such as the attitude of learners, learning environments, instructors, their cultural experiences, as well as their own goals. Recent studies show that learners with strong  motivation  usually  demonstrate  greater  language  competence  in  reading, writing, listening, as well as speaking skills, as this component significantly affects the practice  carried  out  by  learners.  This  study  accentuates  that  motivation  remains  a dynamic  component  that  keeps  on  fluctuating,  and  instructors  must  use  different motivational techniques in order to establish positive environments.